Cool runnings - Steel, Dawn; Turteltaub, John; Siefert, Lynne; Swerdlow, Tommy; Goldberg, Michael (Distributed by Buena Vista Pictures, Int'l., 1993)
Based on a true story, this is the comedic saga of four Jamaican athletes and their coach who compete as bobsled racers at the Calgary Winter Olympics with few resources and virtually no clue about winter sports. With pride, determination, and dignity, the bobsledders make their impossible dreams come true.